Improving the Effect of English Classroom Teaching Based on the Real-Time Supervision of College Students - Wenjing Deng; Bo Jiang (Advances in Multimedia)
This paper proposes a method to improve the effect of English classroom teaching based on the real-time monitoring of college students’ status. Education informatization reinsert teaching evaluation and teaching management methods, use the new generation of information technology to track the entire process of monitoring and teaching, and carry out academic analysis and learning diagnosis, to pay attention to knowledge teaching to more emphasis on the cultivation of ability quality. Behavior analysis can identify students’ classroom behavior in real time to track changes in the state of students. We herein count the classroom status of students and formulate quantitative guidelines and analyze the sequence diagram of each classmate’s class behavior state and statistics from the time and duration of various classroom behaviors in classmates. Each student’s listening quality is scored, and the visual methods such as sequential maps and distributed cake maps are used in class behavior to enable students to understand their own quality of the lesson. By analyzing the laws of student class behavior status distribution, we provide a data-driven mechanism for teacher classroom teaching quality evaluation and teaching method improvement.